Patterns of benzodiazepines use in primary care adults with anxiety disorders. Issue 7 (July 2018) - Tanguay Bernard, Marie-Michèle; Luc, Mireille; Carrier, Jean-Daniel; Fournier, Louise; Duhoux, Arnaud; Côté, Elodie; Lessard, Olivier; Gibeault, Catherine; Bocti, Christian; Roberge, Pasquale
Abstract: Background: Benzodiazepines are among the most commonly prescribed drugs for anxiety disorders. While they are indicated as adjunctive treatment for short-term use according to clinical practice guidelines, previous studies have shown patterns of long-term use of benzodiazepines, which is problematic due to side effects, dependence and potential of abuse. The aims of this study were to examine among a large sample of primary care adults suffering from anxiety disorders: 1) benzodiazepine use patterns; and 2) correlates of long-term benzodiazepine use. Methods: Data were drawn from the "Dialogue" project, a large primary care study conducted in 64 primary care clinics in the province of Quebec, Canada. Following a mental health screening in waiting rooms, patients at risk of anxiety or depression completed the Composite International Diagnostic Interview-Simplified (CIDIS). A sample of 740 adults meeting DSM-IV criteria for Generalized Anxiety Disorder, Panic Disorder or Social Anxiety Disorder in the past 12 months took part in this study. Results: Benzodiazepines were used by 22.6% of participants with anxiety disorders in our primary care sample. A large majority of benzodiazepine users (88.4%) met our indicator of long-term use, as defined by utilization for more than 12 weeks including regular and as-needed use. Based on a logistic regression model, individual correlates associated with long-term benzodiazepine use included: being 30 years or older, having a comorbid physical illness, meeting criteria for comorbid agoraphobia, reporting the use of sleep-aids, and concurrent SSRI utilization. Limitation: Data collection with self-reported questionnaires may be subject to information bias. Conclusions: Despite knowledge of the risks of long-term use of benzodiazepines, this remains a pervasive problem. Clinicians need to be mindful of patterns and risk factors leading to long-term use of benzodiazepines in patients with anxiety disorders. Results of this study should raise awareness regarding appropriate prescription practices for benzodiazepines, including decision-making in initiation, duration of prescription, and use of strategies for discontinuation in current long-term benzodiazepine users.